“Andhap Asor” in a Psychological Perspective: A Realist Study of Contemporary Javanese Society - Munawaroh, Chusnul; Setyawan, Jefri (Jurnal Psikologi Teori dan Terapan, 2024)
Background: Cultural values ​​in Javanese social interactions have shifted, especially in the context of modernization that has an impact on the implementation of Andhap Asor, a cultural concept that emphasizes humility and respect. Objective: This qualitative study aims to explore the meaning and implementation of Andhap Asor in contemporary Javanese society through a realist approach, focusing on the psychological context of this value in social behavior. Method: Data were collected through semi-structured interviews and surveys with open-ended questions, involving teenagers, cultural figures, and stakeholders, selected using purposive sampling techniques. Thematic analysis in this study produced four themes: (1) The Psychological Concept of Andhap Asor; (2) Multi-generational Context in the Implementation of Andhap Asor; (3) Cultural Shift and Preservation Efforts; and (4) Contribution of Andhap Asor to Education and Social Cohesion. Conclusion: The conclusion of the study shows that although the value of Andhap Asor has declined among the younger generation, this principle remains important in creating harmonious social relationships, supporting mental health, and maintaining social cohesion in the modern era.